Right to Reject: A Tool of Augmenting Anarchy over Advancing Democratization & Inclusivity in Political Landscape - Dahal, Atindra (Kathmandu School of Law Review, 2025)
Among many other political events, election significantly underscores democratization and primarily manifests much awaited outcomes. Electing most suitable and competent candidates through election ensures and ascertains the expected course of development in nation. Most of the time, voters unfold deep resentment then resonate over gross failure and apathy of elected candidates and extend an evident opprobrium on such ineffective and nonperforming winner/leaders. The chances of electing the smart, competent and capable representatives will be seriously jeopardized if political parties present same level candidates on electoral grounds. Thus, a new agenda is being urged that there should be provision of right to reject (NOTA) on ballot paper. Hence, voters can outshine or outsmart all candidates in-case they are not worthwhile to elect. Nepal has been passionately having noteworthy preparatory atmosphere to introduce it in upcoming elections, sooner. Considering the same outset, this research work has focused to chart out two major inferences as followings that the: a) Notion of right to reject and its evolution in global political landscape is philosophically a wrong idea. b) Among the probability of advanced democratization & Inclusivity or anarchy that the proposed practice may invite into political landscape of Nepal, the latter visibly prevails over the first.